Softwar and Power Projection in the Digital Age: A Book Review Through the Lens of the Austrian School of Economics - Marcos Giansante (Mises)
This article presents a critical analysis Softwar: A Novel Theory on Power Projection and the National Strategic Significance of Bitcoin by Jason P. Lowery. Structured chapter by chapter, the review aims to contrast the author's proposal—which reinterprets Bitcoin as a strategic tool for state deterrence—with the theoretical foundations of the Austrian School of Economics: Carl Menger, Ludwig von Mises, Friedrich Hayek, Murray Rothbard, and Hans-Hermann Hoppe. This analytical experience extends back in time to influential predecessors such as Adam Smith, Frédéric Bastiat, and Alexis de Tocqueville. The key argument is to show how state appropriation of decentralized technologies like Bitcoin undermines their ethical and functional foundations. The critique is developed under the belief in natural law, spontaneous order, individual liberty, and the uncompromising defense of private property.